Study on conscientiousness, academic self-efficacy and self-esteem predictive power on academic procrastination among counselling students - Ibiam Dike; Stephen Oluwaseun Emmanuel (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The purpose of this study is to investigate the predictive effect of Conscientiousness, Academic Self-Efficacy and Self-Esteem on Academic Procrastination among Counselling Students. Three hundred students studying Counselling in a College of Education in Nigeria, West Africa were selected through the simple random method and completed the measures of Conscientiousness, Academic Self-efficacy, Self-esteem, and Academic Procrastination. The result from the correlation matrix and hierarchical regression model shows that academic procrastination behavior of students is explained by conscientiousness, academic self-efficacy, and self-esteem. It was also shown from the model that all the predictor variables contributed 54% of the total variance in academic procrastination among counselling students. Research results are discussed in the light of related literature and practicable recommendations were provided.